FOTO SEJARAH PADA MEDIA DIGITAL: PEWARNAAN DAN MEME BERKONTEN SEJARAH - Iman Zanatul Haeri (SASDAYA: Gadjah Mada Journal of Humanities, 2019)
Technological developments make it easier for historical reviewers to approach historical sources. But there is a trend in Indonesian digital society to change historical sources such as historical photos as information consumption. Along with the development of the times, analog photos turned into historical photos that were present in the millennial era appeared in two ways; first coloring photo history, the second "meme" set in historical photos. In order to track digital footage of this phenomenon, historical methodology and photo analysis of Roland Barthes are used to show the birth of historical photo coloring trends and memes in the digital world. The coloring of historical photos causes a change in time awareness of historical sources and memes on historical photographs cause a change and multiplication of meanings in digital photos as historical sources.